Estudo comparativo de eficácia terapêutica: dose única semanal x dose convencional diária de sulfato ferroso na anemia ferropriva - Flavio Diniz Capanema (2006)
Introduction: the iron deficiency anemia is a serious problem of public health, over all in pregnant women and children, with major prevalence in developing countries and associated with low social and economics conditions. The knowledge about risk groups, related factors, diagnosis and early treatment could interfere with natural course of the illness preventing potential irreversible damages. The low adhesion of patients to the conventional treatment contributes for the maintenance of high prevalence rates. Some alternatives have been proposed in attempt of better control, being the use of iron in a weekly dose promising for the reduction of collateral effect, with greater adhesion and minor costs in the treatment. Objective: evaluate the effectiveness of single weekly dose of ferrous sulphate in the treatment of iron deficiency anemia compared to the traditional daily dose. Methods: randomized clinical trial conducted between 2001 and 2004 in children aged 0 to 6 years from day-care centers of Eastern Region of Belo Horizonte City. The study got the approval of Ethics Research Committee of Minas Gerais Federal University on April-25-01. In order to select anemic subjects to treatment, a screening was performed using portable hemoglobinometer (Hemocue®). Those with capillary hemoglobin (Hb) lower than 11.5 g/dL were submitted to laboratorial confirmation by eritrogram and ferritin tests. Hb =11.0 g/dL plus microcitose and/or hipocromia were utilized as criteria to define iron deficiency anemia. They were allocated for treatment with ferrous sulphate during 12 weeks, being the group 1 = 4mg/Kg daily and group 2 = 4mg/Kg weekly. In the end, eritrogram and ferritin were performed again. The sample was defined by the Bi-caudal method, with trustworthiness of 95% and power of 90% with minimum of 42 children per group. To compare averages in each group it was used Paired T Student Test and Anova Test for comparison of averages between the groups at the beginning and the end of treatment.Results: from 693 children initially selected, 93 fulfilled the criteria for treatment. In group 1 (daily) 43 had been treated / 2 losses and group 2 (weekly) 44 treated / 4 losses. In daily group was observed significant increases between initial Hb averages (9.77 ± 1.14 g/dL) and final (10.72 ± 0.70 g/dL) and between initial ferritin (17.37 ± 13.84) and final (35.87 ± 17.74). In weekly group it was also observed significant increases from initial Hb averages (9.71 ± 1.17 g/dL) to final (10.37 ± 0.95 g/dL) and from initial ferritin average (16.83 ± 10.45) to final (29.32 ± 15.91). In the end of treatment the comparison between groups showed no significant difference on average of Hb (p-value = 0.112) and ferritin (p-value = 0.073). Conclusion: both therapeutic schemes with ferrous sulphate had shown good reply in the treatment of iron deficiency anemia, with similar effectiviness in relation to increase of variables investigated.